2003
DOI: 10.1104/pp.103.021345
|View full text |Cite
|
Sign up to set email alerts
|

A New Algorithm for Computational Image Analysis of Deformable Motion at High Spatial and Temporal Resolution Applied to Root Growth. Roughly Uniform Elongation in the Meristem and Also, after an Abrupt Acceleration, in the Elongation Zone

Abstract: A requirement for understanding morphogenesis is being able to quantify expansion at the cellular scale. Here, we present new software (RootflowRT) for measuring the expansion profile of a growing root at high spatial and temporal resolution. The software implements an image processing algorithm using a novel combination of optical flow methods for deformable motion. The algorithm operates on a stack of nine images with a given time interval between each (usually 10 s) and quantifies velocity confidently at mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
131
2
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(141 citation statements)
references
References 47 publications
7
131
2
1
Order By: Relevance
“…2A and SI Appendix, Fig. S3C) and calculated that cells enter the elongation zone every ∼0.46 h. These data are consistent with reported growth dynamics (7,32), with the cells' elongation rate being approximately constant throughout the elongation zone and abruptly reducing to zero on progression to the mature zone (SI Appendix, Analytical Model Solutions). Fitting a smooth function, l(x), to the cell length data and using Eq.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…2A and SI Appendix, Fig. S3C) and calculated that cells enter the elongation zone every ∼0.46 h. These data are consistent with reported growth dynamics (7,32), with the cells' elongation rate being approximately constant throughout the elongation zone and abruptly reducing to zero on progression to the mature zone (SI Appendix, Analytical Model Solutions). Fitting a smooth function, l(x), to the cell length data and using Eq.…”
Section: Resultssupporting
confidence: 76%
“…Thus, the interplay between cell growth causing dilution and the dilution affecting the regulation of cell growth can explain the root growth dynamics. Many authors have observed the characteristic pattern of the RER close to the tip of plant roots of many species (7,31,32). Explaining this growth pattern in terms of gibberellin levels being reduced by dilution provides a key insight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent platforms for non-invasive analysis of root growth provide accurate and reliable results with high temporal and spatial resolution (van der Weele et al 2003, Roberts et al 2006, Rahman et al 2007, Walter et al 2009). However, these methods are time-consuming, often targeted and have a low throughput.…”
Section: Introductionmentioning
confidence: 99%
“…In the 90s, new digital cameras and informatics tools enabled the development of automatic tracking algorithms used for particle image velocimetry. RootFlowRT (Van der Weele et al, 2003), Kineroot (Basu et al, 2007), RootTrace (French et al, 2009), GrowthTracer (Iwamoto et al, 2013) and Kymorod (Bastien et al, 2016) are among many recent examples of software dedicated to the monitoring of root growth. However, all particle image velocimetry methods rely on the use of identifiable image texture patterns in each successive picture.…”
mentioning
confidence: 99%